Nexus Between Economic Growth, Renewable Energy, Industry Value Added and CO2 Emissions in ASEAN - Indah Susilowati; M. Silahul Mu'min; Hanny Qudsyina; Hesti Asri Wahyuni; Suci Rismawati; Hapsari Ayu Kusumawardhani; Md. Ruyel Miah (Muhammadiyah University Press, 2023)
This study aims to identify the relationship between economic growth, renewable energy, and industrial value added to CO2 emissions in ASEAN. The data used is panel data of 10 ASEAN countries from 2001-2020. This study uses the vector error correction model (VECM) for analysis. The estimation results show that CO2 emissions are only influenced by the CO2 variable itself in the previous period in the short term. In addition, economic growth and renewable energy significantly negatively affect CO2 emissions in the long term. Economic growth has the largest contribution to reducing CO2 emissions. The empirical findings also support the existence of the environmental Kuznets curve (EKC) in ASEAN. However, industrial value added has no significant effect on CO2 emissions. This study has several policy implications. The government needs to 1) strengthen energy transition regulations to encourage the use of renewable energy, 2) increase investment in RD to stimulate green technology innovation, and 3) protect the environment to mitigate negative externalities of economic activity.